DL-3-n-butylphthalide (NBP) alleviates poststroke cognitive impairment (PSCI) by suppressing neuroinflammation and oxidative stress - Zhang, Hui; Wang, Laifa; Yang, Yongping; Cai, Chuanhai; Wang, Xueqin; Deng, Ling; He, Binsheng; Zhou, Wenhu; Cui, Yanhui (Frontiers in Pharmacology, 2023)
Currently, the recovery of cognitive function has become an essential part of stroke rehabilitation. DL-3-n-butylphthalide (NBP) is a neuroprotective reagent and has been used in stroke treatment. Clinical studies have confirmed that NBP can achieve better cognitive outcomes in ischemic stroke patients than in healthy controls. In this study, we aimed to investigate the influences of NBP on cognitive function in an ischemic reperfusion (I/R) rat model. Our results showed that NBP profoundly decreased neurological scores, reduced cerebral infarct areas and enhanced cerebral blood flow (CBF). NBP potently alleviated poststroke cognitive impairment (PSCI) including depression-like behavior and learning, memory and social cognition impairments, in I/R rats. NBP distinctly suppressed the activation of microglia and astrocytes and improved neuron viability in the ischemic brain. NBP inhibited the expression of inflammatory cytokines, including interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α), by targeting the nuclear factor kappa B/inducible nitric oxide synthase (NF-κB/iNOS) pathway and decreased cerebral oxidative stress factors, including reactive oxygen species (ROS) and malondialdehyde (MDA), by targeting the kelch like ECH associated protein 1/nuclear factor-erythroid 2 p45-related factor 2 (Keap1/Nrf2) pathway in the ischemic brain. The current study revealed that NBP treatment improved neurological function and ameliorated cognitive impairment in I/R rats, possibly by synergistically suppressing inflammation and oxidative stress.